Exploring the effects of temperature and light availability on the vegetative propagation processes of the non-native species Asparagopsis armata - Sainz-Villegas, Samuel; Sánchez-Astráin, Begoña; Puente, Araceli; Juanes, José A. (Frontiers in Marine Science, 2024)
Widespread generalist species, particularly the non-native invasive ones, are expected to be enhanced by climate change resulting in a biotic homogenization of ecosystems. The red seaweed Asparagopsis armata is a non-native opportunistic species, widely distributed in the European coasts of the North Atlantic, where it has been considered invasive. In this work, we examined the effects of temperature and irradiance on the vegetative propagation process of this species in a laboratory experiment. We considered vegetative propagation due to its implications in the invasion process (as it is considered one of the main sources of recruitment). In gametophytes, the process was characterized through the survival rates of hook-shaped specialized structures and the production and growth of new plantlets from hooks of 1-3cm in length. In tetrasporophytes, the growth and phycobiliprotein contents of previously excised tufts was analyzed. For gametophytes, results revealed how vegetative propagation for this species was conditioned by the low survival rates of hooks once detached from the main thallus. In our experiment, survival probabilities after 30 days of culture were always below 50%. Comparisons among environmental conditions showed lower survival rates under increasing levels of temperature and decreasing levels of irradiance. In fact, mass mortality was detected at 18°C and low irradiance, where almost any hook-shaped fragment survived. Nevertheless, patterns of appearance and growth of plantlets at different temperatures and irradiances were not clear. In the case of tetrasporophytes, only positive growth rates were registered at 15°C and 55-60 µmol/m2/s after 30 days of culture. Higher concentration of phycobiliproteins was detected at higher temperatures during the first days of culture, while not clear patterns were detected at the end. In the light of climate change, understanding these reproduction patterns is necessary in order to adopt better management actions in the future.